inggris sistem pendidikan negara belanda: sistem pendidikan - Ade Irma Suryani; Rusdinal Rusdinal; Azwar Ananda; Nurhizrah Gistituati (International Journal Of Humanities Education and Social Sciences (IJHESS), 2023)
The education system in the Netherlands is known as the "mixed education system", which means that there are many types of schools with different teaching methods and philosophies. Nonetheless, there are some basic best practices that characterize education in the Netherlands, the aims of this article are: History of Dutch education, Politics and Educational Objectives, Structure and types of Education, Education Management: Authority, funding, personnel, curriculum and teaching methods, exams, grade increases and certification and evaluation, the method in writing this article uses a literature review where the literature is taken according to the subject matter and is analyzed in depth so that conclusions can be drawn and then the results of writing this article are the education system in The Netherlands uses a collaborative approach, where students in the Netherlands are encouraged to study and work together in groups. Collaboration systems are often an important part of classroom teaching. Schools in the Netherlands are very open and encourage parents to participate in school activities. They also provide various facilities to facilitate the relationship between students, teachers and parents. The curriculum in the Netherlands is very flexible and allows students to adapt their learning experience according to their needs. Students are given many choices and are directed to choose subjects and study programs that suit their interests and inclinations. Education in the Netherlands is highly inclusive, with a wide range of services and support provided for students with special needs or learning challenges. In addition, in the Netherlands there is also free and equal education for everyone, regardless of economic or social status.